Development of a post processor package for structural analysis on a microcomputer. - Rousseau, C. G. W.(Christian Gustav Waldemar) (Stellenbosch : Stellenbosch University, 2012)
Thesis (M.Ing.) -- University of Stellenbosch, 1985.